(untitled) (Agricultural Engineering, 2016)
The primary objective of the experiment was to determine the average coverage of the sprayed liquid on the plant surface according to the adopted coefficient of the spray surface of plants (Wpo). Examinations were performed under laboratory conditions, using a sprayer, which was moving with a constant operating speed, at various operating pressures. During the study four types of nozzles were used: standard and ejector. They sprayed objects, which were artificial plants, equipped with probes in the form of water-sensitive papers. Probes were placed on the horizontal and vertical surfaces of the plants. The degree of coverage was determined by computer image analysis. The analysis of obtained results showed that the coefficient of the surface spray has a significant impact on the size of the average surface coverage of sprayed objects. It was found that in case where the Wpo po > 1, ejector nozzles and standard double may be used more successfully.